PSIX-11 Pioglitazone Hydrochloride Combined with Vitamin E or Chromium-Methionine Improves Meat Quality and Muscle Antioxidant Ability in Finishing Pigs. (7th December 2018) - Jin, C; Gao, C; Wang, Q; Yan, H; Wang, X
Abstract: In the last decades, nutrition redistribution agents have received a great attention because they can improve meat quality. However, the effects of single additives are often poor. Pioglitazone hydrochloride (PGZ) and vitamin E (VE) are know to increase fat deposition and reduce the stress response and improve meat quality. Total of 240 Duroc x Landrace x Large White pigs with the similar weights were randomly divided into 6 groups with 5 replicates in each group and 8 pigs per replicate. The control group (basic diet containing 75 mg/kg VE), PGZ group (basic diet + 15 mg/kg PGZ), VE group (basic diet + 325 mg/kg VE), Met-Cr group (basic diet + 200 μg/kg Met-Cr), PGZ + VE group (basic diet + 15 mg/kg PGZ + 325 mg/kg VE), and PGZ + Met-Cr group (basic diet + 15 mg/kg PGZ + 200 μg/kg Met-Cr). Compared with the control group, the PGZ + Met-Cr group significantly decreased average daily feed intake and feed to gain ratio (P<0.05). Moreover, PGZ + VE supplementation significantly decreased cooking loss (P<0.05) and the IMF content were significantly increased by PGZ + VE and PGZ + Met-Cr supplementation (P<0.05). Furthermore, C18:1n-9c and C18:3n-3 proportions in the PGZ + VE group were significantly greater than that in the control group (P<0.05), and dietary supplemented with PGZ + Met-Cr significantly increased C18:1n-9c proportion too (P<0.05). The polyunsaturated fatty acid (PUFA) proportion was higher in treatment groups than that in the control group (P<0.05). In addition, the superoxide dismutase and glutathione peroxidase activity were increased significantly in the experimental group (P<0.05). Taken together, dietary supplemented with 15 mg/kg PGZ + 325 mg/kg VE or 15 mg/kg PGZ + 200 μg/kg Met-Cr could improve meat quality by increase IMF, PUFA proportions and the muscle antioxidant ability.